The Effect of Organizational Commitment, Compensation, and Workload on Turnover Intention with Job Satisfaction as an Intervening Variable - Citra Pradipta Rinto Putri; Wyati Saddewisasi; Djoko Santoso (Cv. Syntax Corporation Indonesia, 2026)
This study aims to analyze the influence of organizational commitment, compensation and workload on turnover intention, with job satisfaction as an intervening variable at SDIT Harapan Bunda Semarang. The main problems raised in this study are the existence of employees' intention to change jobs (turnover intention) and the differences in the results of previous research regarding the relationship between organizational commitment, compensation and workload to turnover intention. The research method used is a quantitative approach with an explanatory type of research. The population in this study is all 75 employees of SDIT Harapan Bunda Semarang, who were made respondents through the census sample technique. Data collection was carried out with a Likert scale questionnaire, while data analysis used SmartPLS-based Structural Equation Modeling (SEM) version 4.1.1.4 to test the direct and indirect relationships between variables. The results of the study show that organizational commitment does not have a significant effect on turnover intention directly, but has a positive and significant effect on job satisfaction. Compensation and workload have been proven to have a positive and significant effect on turnover intention. Job satisfaction was found to have a positive and significant effect on turnover intention (playing a role in reducing the intention to move). In mediation testing, job satisfaction was able to significantly mediate the relationship between the organization's commitment to turnover intention and the relationship between compensation and turnover intention. However, job satisfaction is not able to mediate the relationship between workload and turnover intention.